Impact of 3D-printed models in meetings with parents of children undergoing interventional cardiac catheterisation - Karsenty, Clément; Hadeed, Khaled; Djeddai, Camelia; Lateyron, Julie; Guitarte, Aitor; Vincent, Remi; DeBarros, Nathalie; Combes, Nicolas; Briot, Jerome; Dulac, Yves; Yrondi, Antoine; Acar, Philippe (Frontiers in Pediatrics, 2023)
Background Paediatric interventional catheterisation has consistently improved in recent decades, with often highly successful outcomes. However, progress is still required in terms of the information delivered to parents and how parental anxiety is managed. Aim To investigate the impact of cardiac printed models on improving parental understanding and alleviating anxiety before interventional catheterisation. Methods The parents of children undergoing interventional cardiac catheterisation were prospectively enrolled in the study. A questionnaire highlighting knowledge and understanding of the condition and cardiac catheterisation per se was scored on a scale of 1–30. The State-Trait Anxiety Inventory (STAI), which generates current anxiety scores, was also used before and after the pre-catheterisation meeting. The “printing group” received an explanation of catheterisation using the device and a three-dimensional (3D) model, while the “control group” received an explanation using only the device and a manual drawing. Results In total, 76 parents of 50 children were randomly assigned to a “control group” (n = 38) or “printing group” (n = 38). The groups were comparable at baseline. The level of understanding and knowledge improved after the “control group” and “printing group” meetings (+5.5±0.8 and +10.2±0.8; p < 0.0001 and p < 0.0001, respectively). A greater improvement was documented in the “printing group” compared to the “control group” (p < 0.0001). The STAI score also improved after the explanation was given to both groups (−1.8±0.6 and −5.6±1.0; p < 0.0001 and p < 0.0001). The greatest improvement was noted in the “printing group” (p = 0.0025). Most of the parents (35/38 from the “printing group”) found the models to be extremely useful. Conclusion 3D-printed models improve parental knowledge and understanding of paediatric cardiac catheterisation, thereby reducing anxiety levels.